2022
DOI: 10.37467/revhuman.v11.4317
|View full text |Cite
|
Sign up to set email alerts
|

Análisis del sexismo y feminismo en el futuro profesorado

Abstract: El presente estudio tiene como objetivo analizar el sexismo y el feminismo en el futuro profesorado. La muestra se compone de 692 personas y los datos se obtienen con la administración de la escala ISA para medir el sexismo ambivalente (hostil y benevolente) y la escala The self-identification as feminis para medir la identificación feminista. Los resultados muestran que los hombres presentan mayores niveles que las mujeres tanto de sexismo hostil como de benevolente, y que las mujeres se identifican más con e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This is not a novel result in the literature. National-level (Fernández et al 2022;Madolell et al 2020) and international studies have confirmed this idea. In fact, the evidence indicates that female university students are more sensitive to questions of gender (Khan et al 2018).…”
Section: Discussionmentioning
confidence: 83%
“…This is not a novel result in the literature. National-level (Fernández et al 2022;Madolell et al 2020) and international studies have confirmed this idea. In fact, the evidence indicates that female university students are more sensitive to questions of gender (Khan et al 2018).…”
Section: Discussionmentioning
confidence: 83%